A STUDY OF THE REPAIR ACTIVITY OF THE XTHA AP ENDONUCLEASE FROM HELICOBACTER PYLORI IN MUTANT ESCHERICHIA COLI - Turgimbayeva , A.M.; Abeldenov , S.K.; Saparbayev , M.K.; Ramankulov , Ye.M.; Khassenov , B.B. (Eurasian Journal of Applied Biotechnology, 2018)
Oxidized and alkylated DNA damage occurs in the Helicobacter pylori genome during its life, just as it does in the genomes of other pathogens. Reactive oxygen species cause single-stranded DNA breaks, and the alkylation of purine bases leads to the formation of an apurinic/apyrimidinic site (AP site). Base excision repair enzymes, in particular AP endonucleases, play an important role in the removal of cytotoxic oxidized DNA damage and AP sites. H. pylori has a single XthA AP-endonuclease (HpXthA), unlike E. coli, which has two. We aimed to obtain rabbit polyclonal antibodies against HpXthA, and optimize western blot conditions with the obtained antibodies. We carried out a comparative analysis of H. pylori xthA gene expression in the pET-system vectors relative to pBlueScript SK(+). We confirmed that the replacement of an aspartic acid residue with an asparagine residue at position 144 is essential for the enzymatic activity of the HpXthA AP endonuclease. We also showed the importance of the HpXthA AP endonuclease in the survival of cells treated with methyl methanesulfonate and hydrogen peroxide. For this, E. coli xthA-, nfo- double mutants were complemented with the xthA gene from H. pylori. As a result of H. pylori xthA gene expression, E. coli survival increased in the presence of mutagens. In mutant E. coli, the repair of oxidized and methylated DNA bases occurred owing to HpXthA expression, which was confirmed by western blotting with anti-HpXthA antibodies.